Pijat Kendiku: Antara Kearifan Lokal dan Kekecewaan terhadap Pengobatan Medis - Agustin Putri Wulansari; Nur Hadi; Joan Hesti Gita Purwasih (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2021)
The current era of modernization has entered every line of human life, including the medical world. However, not all people can reach medical treatment even though the government has provided health service facilities. In line with this, traditional alternative medicine such as massage is still popular to cure ailments among the public. The author tries to raise the reasons why people prefer traditional medicine over medical treatment. This study used qualitative ethnographic methods with data collection techniques that are interviews and observations. The result of the research serves as documentation of cultural features in the health sector that is still developing in society. As an analytical technique, the author used James C. Young's health anthropology perspective. The data analyses used are data collection, data reduction, and data presentation in descriptions. This research showed that people prefer massage as a healing method for many reasons, such as having more affordable prices, being unprepared for the risk of medical treatment, feeling disappointment with medical treatment that does not work, and trusting in personalistic illness